Вдосконалення стратегії фінансового освіти для сталого розвитку - Margvelashvili, Irakli; Kostava, Mariami (Dr. Viktor Koval, 2020)
Introduction. Modern society has long agreed that financial education is one of the pillars of its sustainable development. In many countries, action plans were prepared, strategies developed, training courses were aimed at increasing the level of financial education, but after a few years it is again clear that the problem has not been solved, there are very few examples of success and it is not known whether these successes are the result of the above measures. The need of change the strategies in place today in financial education is slowly emerging. There is an urgent task of improving the strategy of financial education at the present stage of development of society. Aim and tasks. The purpose of this paper is to analyze the current financial education strategy on the example of one particular country – Georgia, its logical consequences and find the levers that will make this strategy more effective or outline the contours of the new strategy. Results. The results of the work done in Georgia in the field of financial education over the past six years were analyzed. Comparison of the stated goals and actual results of the current strategies of financial education is carried out. The study is based on the analysis of the determinants of financial behavior of human, the main postulates of behavioral economics. The methods of logical generalization, synthesis, analysis and deduction are widely used in the research to reveal the cause-and-effect relationship between mental models of thinking, financial education and financial stability of the individual. Also examined the development policy measures adopted by the World Bank. An assessment of their relevance for improving financial education is carried out. The importance of considering mental models of thinking in achieving goals set in various spheres of society was noticed. Also, as a result of the analysis, new approaches were identified that improve the strategy of financial education. Conclusions. Strategies need to be developed based on the mental models of the population of a particular country taking into account the psychological aspects that are significant for the members of a given community. It is necessary to process the information provided by the population, not only semantically, but also etymologically, within the framework of the measures outlined in the strategy and use categories in the context to which the society is more sensitive. More successful examples of financial education development policies need to be considered.